2014
DOI: 10.1002/app.40840
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline‐functionalized magnetic nanoparticles for the removal of toxic dye from wastewater

Abstract: A novel and inexpensive approach was adopted to develop a magnetic nanocomposite for the adsorption of cationic dye from an aqueous solution. This nanocomposite, which was based on a superparamagnetic iron oxide nanocore, was functionalized with a hydrophilic coating of polyaniline (PANI). The nanoparticle size, colloidal stability, surface chemistry, and magnetic properties were studied extensively by transmission electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and vibrating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The Langmuir adsorption is a physical adsorption which suggests the monolayer coverage of dye on PANI-NiFe 2 O 4 nanocomposite. As MB is a cationic dye, there is an electrostatic interaction exists [17,21,22]. From the desorption experiment, it is concluded that the PANI/NiFe 2 O 4 nanocomposite could be recycled and reused.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The Langmuir adsorption is a physical adsorption which suggests the monolayer coverage of dye on PANI-NiFe 2 O 4 nanocomposite. As MB is a cationic dye, there is an electrostatic interaction exists [17,21,22]. From the desorption experiment, it is concluded that the PANI/NiFe 2 O 4 nanocomposite could be recycled and reused.…”
Section: Discussionmentioning
confidence: 93%
“…For reusability, PANI/NiFe 2 O 4 nanocomposite was further separated from the methanol solution using external magnet. The nanocomposite was collected magnetically from the methanol, as the PANI/NiFe 2 O 4 is sufficiently magnetic [22]. The percentage recovery …”
Section: Dye Desorption Experimentsmentioning
confidence: 99%
“…So PANI is frequently used for the removal of dyes from contaminated wastewater. Polyaniline-functionalised magnetic nanoparticles has been used for the removal of toxic dye from wastewater (Mahto et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…2 Network polymers have been increasingly studied for their tunable functionalities, controllable pore geometries and wide range of applications. [35][36][37][38][39][40][41][42] Although conventional polymers and their derivatives, such as poly(acrylic acid), 43 cellulose, 44 carbonaceous materials, 45,46 poly(orthocarbonate), 47 microporous polymers, 48,49 poly(lactic acid), 50 polyaniline, [51][52][53] were used as superabsorbents to remove oils, metal ions, toxic dyes and organic solvents from water, some of these materials were synthesized by using transition metal catalysts and sometimes at high temperatures. 54 Therefore, new, low cost and effective adsorbents are always needed.…”
Section: Introductionmentioning
confidence: 99%